Identification of a novel human circulating metabolite of tenofovir disoproxil fumarate with LC–MS/MS. (April 2015) - Nye, Leanne C; Gray, Nicola; McClure, Myra; Boffit, Marta; Holmes, Elaine; Plumb, Robert S; Wilson, Ian D
Background: Tenofovir disoproxil fumarate (TDF) is an antiretroviral drug used for the treatment of Human Immunodeficiency Virus and Hepatitis B infections.Results: A metabolite that has previously not been observed in the circulation of humans was detected by LC–MS/MS in early time point plasma samples following administration of TDF to healthy volunteers. The metabolite was identified using a range of LC–MS/MS-based techniques as a monoester of TDF, derived from the partially hydrolyzed bis-ester prodrug. TDF, when spiked into plasma, was observed to degrade first to the putative monoester and subsequently to tenofovir.Conclusion: The presence of this unstable metabolite in some samples has implications for sample collection, handling and storage in studies of tenofovir where serum concentrations are determined.